Pengaruh Edukasi Kesehatan Pada Ibu Suku Batak Toba Terhadap Tingkat Pengetahuan Tentang Pencegahan Stunting di Desa Lumban Suhi Suhi Toruan - Helen Kristin Manuela Manik; Harsudianto Silaen (PT. Hasba Edukasi Mandiri, 2025)
Background: The incidence of short toddlers or commonly known as stunting is one of the main nutritional problems experienced by toddlers in Indonesia today. Therefore, short children are a widely accepted predictor of poor quality of human resources, which in turn reduces the productive capacity of a nation in the future. This is caused by various factors, one of which is the mother's lack of knowledge regarding health and nutrition so that the mother cannot take a stand in prevent stunting. According to previous research, lack of maternal knowledge is a factor related to the incidence of stunting in toddlers. Objective: Analyze the effect of health education on mothers' level of knowledge regarding stunting prevention in Lumban Suhi-Suhi Toruan village. Method: the type of research is quantitative with the research design used being pre-experimental research using a one group pre post test design approach. The sampling technique used total sampling with a total of 50 respondents. Analysis of research data used the Wilxocon sign rank test. Results: based on wilcoxon test, the results of this study show that there is a significant effect of education on children's level of knowledge about preventing dental caries with a p-value of 0.00<0.05. Conclusion: there is a significant influence of education on the level of maternal knowledge regarding stunting prevention in Lumban Suhi-Suhi Toruan in 2024. Suggestion: for further research, it is hoped that further research will be carried out by adding other variables such as maternal parenting patterns and maternal attitudes in preventing stunting.